Tracheobronchial injuries in chest trauma: a 17-year experience - SAAD JR,ROBERTO (2017)
ABSTRACT Objective: to discuss the clinical and therapeutic aspects of tracheobronchial lesions in victims of thoracic trauma. Methods: we analyzed the medical records of patients with tracheobronchial lesions treated at the São Paulo Holy Home from April 1991 to June 2008. We established patients' severity through physiological (RTS) and anatomical trauma indices (ISS, PTTI). We used TRISS (Trauma Revised Injury Severity Score) to evaluate the probability of survival. Results: nine patients had tracheobronchial lesions, all males, aged between 17 and 38 years. The mean values ​​of the trauma indices were: RTS - 6.8; ISS - 38; PTTI - 20.0; and TRISS - 0.78. Regarding the clinical picture, six patients displayed only emphysema of the thoracic wall or the mediastinum and three presented with hemodynamic or respiratory instability. The time interval from patient admission to diagnosis ranged from one hour to three days. Cervicotomy was performed in two patients and thoracotomy, in seven (77.7%), being bilateral in one case. Length of hospitalization ranged from nine to 60 days, mean of 21. Complications appeared in four patients (44%) and mortality was nil. Conclusion: tracheobronchial tree trauma is rare, it can evolve with few symptoms, which makes immediate diagnosis difficult, and presents a high rate of complications, although with low mortality.